Welcome to our community

Be a part of something great, join today!

Generating a sequence

  • Thread starter
  • Admin
  • #1

MarkFL

Administrator
Staff member
Feb 24, 2012
13,775
It can be shown that when $5n+1$ and $7n+1$ (where $n\in\mathbb{N}$) are both perfect squares, then $n$ is divisible by $24$.

Find a method for generating all such $n$.
 

Opalg

MHB Oldtimer
Staff member
Feb 7, 2012
2,702
It can be shown that when $5n+1$ and $7n+1$ (where $n\in\mathbb{N}$) are both perfect squares, then $n$ is divisible by $24$.

Find a method for generating all such $n$.
Partial solution:
If $5n+1=p^2$ and $7n+1=q^2$ then $35n+7 = 7p^2$ and $35n+5 = 5q^2$. Subtract, to get $7p^2 - 5q^2 = 2$. That is a Diophantine equation, which you can solve by looking at the continued fraction expansion of $\sqrt{5/7}$. If the $k$th solution is $(p_k,q_k)$, then the first few solutions, with the corresponding values $n_k$ of $n$ are $$\begin{array}{c|c|c|c}p_k&q_k&n_k&n_k/24 \\ \hline 1&1&0&0 \\ 11&13&24&1 \\ 131 & 155 & 3432 & 143 \\ 1561 & 1847 & 487344 & 20306 \\18601 & 22009 & 69199440 & 2883310 \end{array}$$

The numbers $p_k$ satisfy the recurrence relation $p_k = 12p_{k-1} - p_{k-2}$, and $q_k$ satisfies the same recurrence relation. That enables you to generate all the values of $n$, but I have not been able to find an explicit formula for $n_k.$
 
  • Thread starter
  • Admin
  • #3

MarkFL

Administrator
Staff member
Feb 24, 2012
13,775
Partial solution:
If $5n+1=p^2$ and $7n+1=q^2$ then $35n+7 = 7p^2$ and $35n+5 = 5q^2$. Subtract, to get $7p^2 - 5q^2 = 2$. That is a Diophantine equation, which you can solve by looking at the continued fraction expansion of $\sqrt{5/7}$. If the $k$th solution is $(p_k,q_k)$, then the first few solutions, with the corresponding values $n_k$ of $n$ are $$\begin{array}{c|c|c|c}p_k&q_k&n_k&n_k/24 \\ \hline 1&1&0&0 \\ 11&13&24&1 \\ 131 & 155 & 3432 & 143 \\ 1561 & 1847 & 487344 & 20306 \\18601 & 22009 & 69199440 & 2883310 \end{array}$$

The numbers $p_k$ satisfy the recurrence relation $p_k = 12p_{k-1} - p_{k-2}$, and $q_k$ satisfies the same recurrence relation. That enables you to generate all the values of $n$, but I have not been able to find an explicit formula for $n_k.$
Good work, Opalg! (Clapping)

I was not necessarily asking for a closed form solution; a recursive algorithm fits the bill for finding a method to generate the sequence. :D

I will post my solution within 24 hours. (Nerd)
 
  • Thread starter
  • Admin
  • #4

MarkFL

Administrator
Staff member
Feb 24, 2012
13,775
My solution:

Let:

(1) \(\displaystyle 5n+1=p^2\)

Since both squares have the same parity, their difference is even, and so we may let:

(2) \(\displaystyle 7n+1=(p+2k)^2\) where \(\displaystyle k\in\mathbb{N}\)

Subtracting (1) from (2), we obtain:

\(\displaystyle 2n=(p+2k+p)(p+2k-p)=4k(p+k)\)

\(\displaystyle n=2k(p+k)\)

Substituting for $n$ into (1), we have:

\(\displaystyle 5(2k(p+k))+1=p^2\)

\(\displaystyle p^2-10kp-\left(10k^2+1 \right)=0\)

Taking the positive root for $p$, we obtain:

\(\displaystyle p=5k+\sqrt{35k^2+1}\)

A sequence defined recursively by:

\(\displaystyle A_{n+1}=sA_{n}+tA_{n-1}\)

will have limiting values of:

\(\displaystyle L=\lim_{n\to\pm\infty}\frac{A_{n+1}}{A_{n}}=\frac{s\pm\sqrt{s^2+4t}}{2}\)

Observing that for \(\displaystyle s=12,t=-1\) we have:

\(\displaystyle L=\lim_{n\to\pm\infty}\frac{A_{n+1}}{A_{n}}=6\pm \sqrt{35}\)

Thus, we find $p$ may be given in closed form by:

\(\displaystyle p_{m}=c_1\left(6+\sqrt{35} \right)^m+c_2\left(6-\sqrt{35} \right)^m\) where $p_0=1,\,p_1=11$

The initial values are obtained from $n=0,\,24$. We may now determine the parameters $c_i$ from the initial values:

\(\displaystyle p_{0}=c_1+c_2=1\,\therefore\,c_2=1-c_1\)

\(\displaystyle p_{1}=c_1\left(6+\sqrt{35} \right)+\left(1-c_1 \right)\left(6-\sqrt{35} \right)=11\)

Hence:

\(\displaystyle c_1=\frac{7+\sqrt{35}}{14},\,c_2=\frac{7-\sqrt{35}}{14}\)

And so we have:

\(\displaystyle p_{m}=\frac{1}{14}\left(\left(7+\sqrt{35} \right)\left(6+\sqrt{35} \right)^m+\left(7-\sqrt{35} \right)\left(6-\sqrt{35} \right)^m \right)\)

Now, using the relationship between $n$ and $p$ in (1), we have:

\(\displaystyle n=\frac{p^2-1}{5}\)

Hence:

\(\displaystyle n_m=\frac{\left(\frac{1}{14}\left(\left(7+\sqrt{35} \right)\left(6+\sqrt{35} \right)^m+\left(7-\sqrt{35} \right)\left(6-\sqrt{35} \right)^m \right) \right)^2-1}{5}\)
 

alane1994

Active member
Oct 16, 2012
126
And this is yet another example of why I am an engineering major...
Sorry for interrupting with a somewhat "useless" post. Carry on.
 
  • Thread starter
  • Admin
  • #6

MarkFL

Administrator
Staff member
Feb 24, 2012
13,775
And this is yet another example of why I am an engineering major...
Sorry for interrupting with a somewhat "useless" post. Carry on.
Difference equations...they're comin' for ya... (Devil) (Tauri) (Giggle)
 

Klaas van Aarsen

MHB Seeker
Staff member
Mar 5, 2012
8,774
And this is yet another example of why I am an engineering major...
Sorry for interrupting with a somewhat "useless" post. Carry on.
Weren't you posting problems with differential equations?
I found this post by masters rather funny and very true.
Sorry for another interrupting an somewhat useless post. :eek: